ANALISIS PERTANGGUNG JAWABAN HUKUM TERHADAP PEREDARAN KOSMETIK KRIM WAJAH TANPA IZIN EDAR MENURUT UNDANG-UNDANG KESEHATAN DI INDONESIA - Fathanisa, Aulia; Khoiriyah, Azzahra Nur; Afifah, Alya Nurul; Alifah; Illahi, Bhunga Shazkia (Ganesha Civic Education Journal, 2026)
The distribution of facial cream cosmetics without marketing authorization in Indonesia remains a serious problem that has the potential to endanger consumer health. This study aims to analyze the legal accountability of perpetrators and the effectiveness of law enforcement based on the Health Law and the Consumer Protection Law. The method used is normative legal research with a regulatory and contextual approach. The results show that perpetrators can be held accountable for criminal, civil, and administrative offenses, but law enforcement is still hampered by weak oversight and low public legal awareness